DETERMINATION MACROECONOMICS VARIABLES AND STOCK RETURN A CASE OF FINANCE SECTOR AND TRADING & SERVICE SECTOR IN MALAYSIA - Chee, Pauline (Universiti Malaysia Sarawak, UNIMAS, 2011)
The study investigate the interaction between stock return, inflation rate, money supply, industrial production and oil price in finance sector and trading & service sector in Malaysia. The time period start from January 1998 to December 2010. The test that are conducted in the study included Augmented Dickey-Fuller (ADF) unit root test , Phillip-Perron(PP) unit root test, Johansen and Juselius cointegration test, VECM granger causality test and Granger Causality test. The finding are: first, the long run cointegration exist in sector and trading & service sector. Secondly, there is short run relationship between money supply and stock return for finance sector. Thirdly, the oil price and inflation rate has impact on stock return for trading & service sector in short time period. Fourth, the stock return for sector will behave differently in economics condition. The policy recommendation have discussed in the study.